PENDEKATAN KONSTRUKTIVISTIK GURU PAI DALAM MENGATASI PERMASALAHAN RANAH KOGNITIF SISWA TUNA GRAHITA DI SMK NEGERI 17 JAKARTA BARAT - Rihlah Saiidah; Busahdiar (STKIP Subang, 2026)
Cognitive domain issues can manifest in various forms and levels of severity. Primary problems include difficulties understanding basic concepts, low logical and critical thinking skills, a lack of problem-solving initiative, and challenges in applying acquired knowledge, particularly for students with intellectual disabilities (tuna grahita) at SMK Negeri 17 West Jakarta. Often, students struggle to comprehend core concepts; they may memorize definitions but lack a true understanding of their practical application. This research employs a qualitative method with a case study design. Primary data sources include the Vice Principal of Curriculum and Islamic Education (PAI) teachers at SMK Negeri 17 West Jakarta. Secondary data were gathered through interviews with students with intellectual disabilities, as well as literature reviews of books and journals related to constructivist approaches, the cognitive domain, and intellectual disabilities. Data collection involved interviews, observation, and document studies. Data analysis utilized data reduction, data display, and conclusion drawing. Research findings indicate that: 1) The implementation of the constructivist approach by PAI teachers occurs through storytelling sessions regarding real-life events linked to the material. 2) This implementation resulted in increased student activity during learning. 3) Obstacles include complex internal cognitive barriers, such as short-term memory deficits, the unavailability of special education teachers (guru pendamping khusus), and limited projector facilities. Solutions involve simplifying material into concrete behavioral examples relevant to daily life, utilizing creative visual media like Canva, and strengthening cross-sector synergy between PAI teachers, homeroom teachers, and guidance counselors (BK).